Economic Analysis of Cashew Nuts Marketing among Produce Buyers - A. Zubair, Zulaihatu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The study analyzed the economic analysis of cashew nuts marketing among produce buyers in Dekina Local Government Area of Kogi State. Two agricultural zones were purposively selected for the study within the local government areas. The subjects were selected randomly from each of the zones. A total of 125 respondents were randomly selected from the produce buyers for the survey. The primary data was collected with questionnaires and focus group discussion. Data were analyzed using descriptive statistics gross margin analysis and multiple regression analysis. The major means of distribution of cashew nut is from producers to wholesalers. Personal savings dominated the source of capital for producers. Majority of the producers, about 62.4% respondents are educated. From the average cost and returns of cashew nut marketing, the result indicates that the cashew nut has net profit of N2,022,500. The return on capital invested was N1.78 meaning that for every N1 invested on cashew nut marketing N1.78 is realized indicating it is a profitable business. However, the constraints faced by the cashew producer buyer was poor pricing, inadequate credit facilities, bad assess road and lack of storage facilities. It is recommended that marketers are to ensure quality nuts devoid of immature and deformed ones, maintain quality drying process, sorting, and packaging to enhance quality and hence profitability. In addition, the government should encourage private sector to invest in the establishment of cashew industry to promote quality cashew product, which will enhance standard local content for export supply.